Macroscopic Analysis of Fluid Mixing Characteristics of Several Impellers - Lei HUANG; Shaoying ZHU; Yu ZHANG; Liai CHEN (Liaoning Shiyou Huagong Daxue xuebao, 2025)
In order to enrich the understanding of the mixing characteristics of various stirring paddles, the effects of rotational speed and immersion depth of six types of stirring paddles such as Paddle Straight Blade Paddle, Paddle Inclined Blade Paddle, Six Straight Blade Turbine Paddle, Six Inclined Blade Turbine Paddle, Straight Blade Rushton Paddle (Disc Straight Blade Turbine Paddle), Inclined Blade Rushton Paddle (Disc Inclined Blade Turbine Paddle ), on the mixing time, power, power quasi⁃counts, the number of mixing times, the number of mixing efficiencies, have been analyzed in depth. The results showed that the mixing time, power, power quasi number, mixing time number and mixing efficiency number were affected by the rotational speed and submergence depth of six types of stirring paddles. When the rotational speed of the paddle is 150 r/min, the mixing time decreases and then increases with the increase of the submergence depth, in which the power required by the inclined⁃blade Rushton paddle is the smallest, the mixing rate is the largest, and the mixing efficiency is the highest; when the submergence depth is 25 cm, the mixing time of the six types of paddles decreases with the increase of rotational speed, and the power required by the inclined⁃blade Rushton paddle is the smallest, the mixing rate is the largest, and the mixing efficiency is the highest; and the mixing time of the six types of paddles is the largest. When the rotational speed and submergence depth are certain, the power required by the Rushton paddle is the smallest and the mixing efficiency is the highest; the integrated mixing performance of the Rushton paddle is the best. The results of the study provide both experimental data for the industrial applications and a theoretical basis for the optimization of the subsequent design of stirring paddles.